The Relationship Between Personal Factors and Women Preferences Towards Tenun Ikat - Winasis, Indahtyas; Purwanegara, Mustika Sufiati (Journal of Business and Management, 2014)
Indonesia is the largest archipelago in the world that contributes to the richness of textiles tradition. The market of local textile is growing, knowing the fact that there are a lot of potential productions in many regions in Indonesia, such as batik and kebaya. Unfortunately, the exploration of tenun ikat in fashion world is not that much rather than batik and kebaya, whereas major production and usage of tenun ikat is actually big. Therefore, it has to be developed, as tenun ikat definitely has an opportunity in the market, and this final project will be focusing on the preferences towards Tenun Ikat by identifying personal factors’ relationship to consumption behavior towards tenun ikat. The research was executed in Jakarta, Bandung, Central Indonesia, and East Indonesia. Questionnaire regarding personal factors, awareness, consumption behavior, and consumer preferences were filled by 200 female respondents in age range 17 – over 50 years old who interested in Tenun ikat as the object of the research. The data collected is analyzed using Microsoft Excel, IBM’s SPSS 20.0 tool for Mac and processed through Frequency analysis, Cross-tab chi-square analysis, Multivariate: Post Hoc Test Analysis, ONE-WAY ANOVA, and Discriminant. The result found that women are aware of the visual aesthetic product design, and all women in all group of age, group of city origin, group of occupation, and group of monthly expense are used to use tenun ikat as utilitarian goods. It turns out they are already aware of the use tenun ikat for fashion. So, tenun ikat for fashion is definitely has a big opportunity.Keywords: cultural heritage, consumer preferences, consumption behavior, personal factors